Buprenorphine and its formulations: a comprehensive review - Salomon Poliwoda; Nazir Noor; Jack S. Jenkins; Cain W. Stark; Mattie Steib; Jamal Hasoon; Giustino Varrassi; Ivan Urits; Omar Viswanath; Adam M. Kaye; Alan D Kaye (Health Psychology Research)
Buprenorphine, a novel long-acting analgesic, was developed with the intention of two purposes: analgesia and opioid use disorder. Regarding its pharmacodynamics, it is a partial agonist at mu receptors, an inverse agonist at kappa receptors, and an antagonist at delta receptors. For the purpose of analgesia, three formulations of buprenorphine were developed: IV/IM injectable formulation (Buprenex®), transdermal patch formulation (Butrans®), and buccal film formulation (Belbuca®). Related to opioid dependence, the formulations developed were subcutaneous extended release (Sublocade®), subdermal implant (Probuphine®), and sublingual tablets (Subutex®). Lastly, in order to avoid misuse of buprenorphine for opioid dependence, two combination formulations paired with naloxone were developed: film formulation (Suboxone®) and tablet formulation (Zubsolv®). In this review, we present details of each formulation along with their similarities and differences between each other and clinical considerations.